Unraveling the Qurans Linguistic Layers: A Holistic Exploration of Its Sound Structure and Meaning - Isnainiyah; Nasrulloh; Nurul Ainiy; Naif R. Aljohani (https://unikhams.ac.id/, 2025)
Background: Many discussions on the Qurans language focus on one linguistic aspect at a time, leaving the relationship between sound, structure, and meaning only lightly touched. Yet the strength of Quranic expression often comes from how these elements meet and support one another. Aims: This study seeks to understand how different layers of language, its sounds, word forms, sentence patterns, meanings, and rhetorical touches, come together to shape the tone and depth of the Quranic message. The intention is to see the text as a living linguistic whole rather than a set of separated features. Methods: Using a descriptive qualitative approach, several passages are examined through close reading. Attention is given to how particular sounds create emphasis, how word formations expand or narrow meaning, and how sentence order shapes the flow of an idea. These observations are then compared thematically to trace recurring tendencies across the text. Result: The analysis suggests that phonological choices often act as emotional cues. Morphology adds density to meaning, while shifts in syntax draw attention to specific ideas. Layers of semantic and rhetorical expression widen the space for interpretation. Together, these elements reveal a coordinated linguistic system rather than independent parts. Conclusion: The study shows that Quranic language works through an intertwined structure of sound, form, and meaning. This perspective offers a more holistic way to read the text and opens opportunities for further research on how language influences readers understanding and emotional response.